La planificación didáctica de las ciencias naturales y el desarrollo de destrezas con criterios de desempeño en los estudiantes del octavo año de educación general básica, del colegio técnico agropecuario Chaguarpamba, cantón Chaguarpamba, provincia de Loja durante el periodo 2012-2013. Lineamientos alternativos - Camacho Cuenca, Diego Yovany (2014)
Instructional planning allows for reflection and make timely decisions , be clear about what learning needs of each student , what to bring to the classroom and how to organize methodological strategies , projects and processes for learning to be acquired by all, and this way to pay attention to the diversity of students. This research report titled: The Teaching of Natural Sciences Planning and Development Skills with Performance Criteria in the eighth year students of Basic General Education Agricultural Technical School " Chaguarpamba " Chaguarpamba Canton province of Loja. Semester 2012-2013 Alternative Guidelines. It had as its overall objective :To analyze the relationship between the teaching of natural science planning , and development of skills with Performance Criteria in the eighth year students of Basic General Education Agricultural Technical School " Chaguarpamba " . It was an investigation of analytical and descriptive character, the same that focused on an analysis of instructional planning , a very important aspect listed including as the basic tool of teaching, because it is one that allows you to guide, organize and integrate knowledge the teaching-learning process . - Inductive, hermeneutic- dialectical, analytic - synthetic scientific method, descriptive, inferential: For data collection methods such as used. A self employed techniques as interviewing, direct and indirect observation of practical classes of Natural Sciences and the survey that was applied to both teachers and students of the eighth year of EGB the aforementioned school. It is important to state that we worked with two teachers and 70 students, between the results obtained, it was evident that educational planning is not fully structured, lacks elements such as precision teaching and learning, critical evaluation indicators, literature and observations. Also there are restrictions at the time of the formulation of the objectives of the class. Planning performing teachers is taken into consideration as a requirement to submit to the authorities. These in turn do not review them carefully and do they know the weaknesses and strengths Also no action or proceeding for students to develop skills with performance criteria applies, and that teachers have some doubt regarding this important aspect. Finally, do not prioritize those that are characteristic of natural science features traditional skills like memorizing and repeating system is still developing.